Analysis of Gamification in Cybersecurity Education for Students: A Systematic Literature Review - Sodikin, Reisa Aulia; Hikmawan, Rizki (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The increasingly complex digital era requires a deeper comprehension of cybersecurity threats, particularly in educational settings. The imperative to establish an interactive and adaptive learning environment, responsive to technological advancements, makes the adoption of gamification elements as an innovative method to heighten student involvement and deliver crucial knowledge in the context of cybersecurity. To tackle these challenges, this research outlines the cause-and-effect relationships, focusing on the connection between the evolution of cybersecurity knowledge areas and gamification elements found in earlier literature. By specifying the components of the CIA Triadâ€”Confidentiality, Integrity, and Availabilityâ€”this study establishes a strong foundation for investigating how gamification elements can harmonize with the cybersecurity requirements in this digital era. The research utilizes a systematic literature review method based on inclusion and exclusion criteria, the research identifies 13 Google Scholar-indexed articles published between 2018 and 2023. These findings reveal a correlation between gamification elements and the CIA Triad aspects, along with Venn diagrams in recent cyber threats and attacks. This offers a foundation for the development of more potent pedagogical approaches in delivering cybersecurity materials to the generation maturing in this digital era.Era digital yang semakin kompleks menuntut pemahaman yang lebih mendalam terhadap ancaman keamanan siber, khususnya di lingkungan pendidikan. Adapun kebutuhan untuk menciptakan lingkungan pembelajaran yang menarik dan responsif terhadap perkembangan teknologi informasi mendorong penerapan elemen-elemen gamifikasi sebagai metode inovatif yang dapat meningkatkan keterlibatan siswa dan menyampaikan pengetahuan krusial dalam konteks keamanan siber.Â Dalam rangka mengatasi tantangan ini, penelitian ini menjelaskan secara rinci pola sebab dan akibat, dengan fokus pada korelasi antara pengembangan area wawasan keamanan siber dengan elemen-elemen gamifikasi dalam literatur terdahulu. Dengan merinci aspek-aspek CIA Triad, yakni Confidentiality, Integrity, dan Availability, penelitian ini menciptakan dasar yang kuat untuk mengeksplorasi bagaimana elemen-elemen gamifikasi dapat menyelaraskan diri dengan kebutuhan keamanan siber di era digital ini. Penelitian ini menggunakan metode systematic literature review berdasarkan kriteria inklusi dan eksklusi, menghasilkan 13 artikel terindeks Google Scholar yang diterbitkan di tahun 2018-2023. Hasil penelitian menunjukkan adanya korelasi antara elemen-elemen gamifikasi dan aspek CIA Triad, serta diagram venn yang mengilustrasikan kesesuaian elemen gamifikasi dengan aspek CIA Triad pada ancaman dan serangan siber terbaru sehingga dapat memberikan landasan untuk pengembangan pedagogi yang lebih efektif dalam menyampaikan materi keamanan siber kepada generasi yang tumbuh dalam era digital ini.